The application of scanning electron microscope and melt flow index for orange peel in laser sintering process - Wan Yusoff, Wan Ahmad Yusmawiza (Institute of Advanced Engineering and Science, 2017)
In manufacturing, many products need to undergo increasing customisation, and a shortening of the manufacturing cycle time. This makes the time needed to produce prototypes one of the most important contributors to product development cycles. Rapid Prototyping (RP) offers the user the ability to optimise part design in order to meet customer requirements with few manufacturing restrictions. One of the most common RP processes is Laser Sintering (LS). A problem with LS is that sometimes the surface of the parts produced displays a texture similar to that of the skin of an orange (the so-called orange peel texture). This problem must be addressed before the technology can gain wider acceptance. The main aim of this research is to develop a methodology of controlling the input material properties that will ensure consistent and good quality of the fabricated parts. From the experiment, it was found that PA12 powder with high melt flow rate, low melting temperature, low glass transition temperature and low degree of crystallization temperature could improve the sintering process to produce a good Laser Sintering (LS) parts with lower shrinkage rate. The powder which has higher melt viscosity and lower melting heat becomes liquid more easily and therefore flows better during the sintering process due to a shorter chain molecular structure. The results of experimental work indicate that the melt viscosity, and part surface finish are correlated. © 2017 Institute of Advanced Engineering and Science